'A Luminous Translation': Lithophanes at Woburn Abbey, 1836 to 1838. Issue 2 (3rd May 2020) - Scott, Samantha
Abstract : Between 1836 and 1838, a unique display of 175 lithophanes was created at Woburn Abbey by John Russell, 6th Duke of Bedford. Lithophanes (thin porcelain plaques with a relief surface that reveals an image once backlit) were invented around 1826 and primarily reproduced imagery from other sculptures, paintings and prints. Arguing that lithophanes were indicative of English reception of continental imagery, and at the intersection of fine and decorative arts, this article examines the curation of the Woburn lithophanes to show how novelty emblematized the peak of innovation in interdisciplinarity and emerging design reform ideals in the nineteenth century.